Porous or non-porous? The challenge of studying unusual placoid sensilla of Megaphragma wasps (Hymenoptera, Trichogrammatidae) with electron microscopy - Anna V. Diakova; Alexey A. Polilov (Journal of Hymenoptera Research, 2021)
Extreme miniaturization implies a high degree of optimization, rendering the retention of non-functional organs almost impossible. Two unique non-porous placoid sensilla on the antennae of females of Megaphragma were described in the literature. Placoid sensilla in Hymenoptera have an olfactory function and always bear pores; the apparent absence of pores therefore raises the questions whether such sensilla are functional in Megaphragma and whether their surface sculpture had been sufficiently well examined. We examined in detail the external microsculpture and internal ultrastructure of the placoid sensilla using Focused Ion Beam Scanning Electron Microscopy and Scanning Electron Microscopy with various types of sputtering and show that these sensilla actually have a porous cuticle and are innervated by 11 or 12 neurons with branched cilia, which is typical of olfactory sensilla. Comparison of various methods of electron microscopy allows us to conclude that for an accurate determination of the morphofunctional types of sensilla, especially in miniature insects, it is necessary to study both the internal ultrastructure of the sensilla and their external morphology using carefully selected scanning electron microscopy methods.